2010
DOI: 10.1073/pnas.1013083107
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly efficacious vaccinia-based dual vaccine against smallpox and anthrax, two important bioterror entities

Abstract: Bioterrorism poses a daunting challenge to global security and public health in the 21st century. Variola major virus, the etiological agent of smallpox, and Bacillus anthracis, the bacterial pathogen responsible for anthrax, remain at the apex of potential pathogens that could be used in a bioterror attack to inflict mass casualties. Although licensed vaccines are available for both smallpox and anthrax, because of inadequacies associated with each of these vaccines, serious concerns remain as to the deployab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
(33 reference statements)
3
24
0
Order By: Relevance
“…[6][7][8] Recently we reported that a cohort of rabbits immunized with a vaccinia-based PA vaccine created by the integration of the pag gene and an immune enhancing cytokine IL-15 into the genome of licensed smallpox vaccine (Wyeth/IL-15/PA), conferred sterile protection against an inhalation challenge exceeding 200 LD 50 of fully virulent Ames strain (A0462; pXO1 + pXO2 + ) spores. 9 The absence of bacteremia was also observed in the positive comparator group vaccinated with AVA suggesting perhaps PA based vaccines protect vaccinated subjects from inhalation anthrax by aborting the early events of the establishment of B. anthracis infection in the respiratory tract. 9 To explore this intriguing possibility in depth, first we examined the daily body temperature fluctuations in the rabbits that were subjected to the inhalation spore challenge as progressively rising body temperature is a consistent clinical manifestation in rabbits infected with B. anthracis via the inhalation route and parallels bacterial growth and toxin release.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…[6][7][8] Recently we reported that a cohort of rabbits immunized with a vaccinia-based PA vaccine created by the integration of the pag gene and an immune enhancing cytokine IL-15 into the genome of licensed smallpox vaccine (Wyeth/IL-15/PA), conferred sterile protection against an inhalation challenge exceeding 200 LD 50 of fully virulent Ames strain (A0462; pXO1 + pXO2 + ) spores. 9 The absence of bacteremia was also observed in the positive comparator group vaccinated with AVA suggesting perhaps PA based vaccines protect vaccinated subjects from inhalation anthrax by aborting the early events of the establishment of B. anthracis infection in the respiratory tract. 9 To explore this intriguing possibility in depth, first we examined the daily body temperature fluctuations in the rabbits that were subjected to the inhalation spore challenge as progressively rising body temperature is a consistent clinical manifestation in rabbits infected with B. anthracis via the inhalation route and parallels bacterial growth and toxin release.…”
Section: Introductionmentioning
confidence: 81%
“…9 The absence of bacteremia was also observed in the positive comparator group vaccinated with AVA suggesting perhaps PA based vaccines protect vaccinated subjects from inhalation anthrax by aborting the early events of the establishment of B. anthracis infection in the respiratory tract. 9 To explore this intriguing possibility in depth, first we examined the daily body temperature fluctuations in the rabbits that were subjected to the inhalation spore challenge as progressively rising body temperature is a consistent clinical manifestation in rabbits infected with B. anthracis via the inhalation route and parallels bacterial growth and toxin release. 10 The mean body temperature of the three groups of rabbits were similar prior to the inhalation spore challenge, for example, 24 h before the spore challenge, the mean body temperature of the Wyeth/IL-15/PA group was 102.14°F (SD 0.62), whereas the AVA group and the control group displayed a mean body temperature of 102.07°F (SD 0.58) and 102.80°F (SD 0.34) respectively.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations